Evaluating the share performance of socially responsible investment on the Johannesburg Stock Exchange - Cormack, Bradley Alexander (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
Socially responsible investing (SRI) integrates environmental, social and governance (ESG) issues into the investment decision-making process. Growing ESG concerns and the uncovering of corporate scandals have catalysed the substantial growth in SRI portfolios worldwide. Notwithstanding its increasing popularity, barriers to further SRI growth have been identified. Traditional investing practices suggest that theoretically, SRI may underperform conventional investment strategies. However, despite the vast amount of literature on SRI, empirical studies have yielded a mixture of results regarding fund performance. The JSE SRI Index was launched in 2004 to promote transparent business practices. It was discontinued at the end of 2015 succeeded by a new Responsible Investment Index established by the JSE in association with FTSE Russell. The aim of the research was to evaluate the share performance of the JSE SRI Index from 2004-2015. Additionally, the indices were categorised by environmental impact to further analyse disparity among share returns. The study was also divided into two sub-periods, 2004-2009 and 2010-2015, with the latter following the endorsement of integrated reporting by the King III Code as a listing requirement in 2010. A single-factor Capital Asset Pricing Model (CAPM) was used to assess differences in risk-adjusted returns. Engle-Granger and Johansen tests were employed to explore the possibility of a cointegrating relationship between the indices. No significant difference between returns was observed for 2004-2009, with the SRI Index exhibiting statistically significant inferior risk-adjusted returns for the latter half of the study. Overall, a significant difference between share returns was found, with CAPM results suggesting that the JSE SRI Index underperformed the All Share Index by -2.33% per annum throughout the time span of the study. Engle-Granger and Johansen test results indicated the existence of a cointegrating relationship over the first half of the study. However, there was no cointegration between the two indices for 2004-2015, which may be attributed to no significant relationship found for the latter years. Results support the notion that investors pay the price to invest ethically on the JSE. Inferior risk-adjusted returns associated with SRI may be a major barrier to its development in South African markets.
Keywords: Investments -- Moral and ethical aspects -- South Africa; Johannesburg Stock Exchange; Social responsibility of business -- Standards; Social responsiblity of business -- South Africa